The role of innovation culture in shaping innovative behaviour among students at Higher Education Institutions in Malaysia / Siti Hajar Mohd Roffeei - Siti Hajar, Mohd Roffeei (2017)
Guided by the concept of organisational culture and behaviour from the management field of study and applied to the context of higher education, this study examines the antecedents of innovation culture and proposes a conceptual model to understand the relationship between innovation culture and innovative behaviour among Malaysian undergraduate students. The model consists of five constructs: effective communications, climate for innovation, self-efficacy, culture of innovation, and innovative behaviour. Using the cluster sampling techniques, a 6-point Likert scale survey questionnaire was administrated to 1,110 undergraduate students of five public research universities in Malaysia. The questionnaire contains 48 items that measured the five research constructs. Results indicated that self-efficacy is a major antecedent of innovation culture followed by effective communications and climate for innovation. The findings also revealed that innovation culture had a positive effect and significantly influenced innovative behaviour. Climate for innovation on the other hand, was found to have no significant effect on innovative behaviour. The result signifies the importance of effective communications and self-belief in moulding the intended behaviour regardless of the situations or environmental conditions. The key finding of this study was the importance of self-efficacy in encouraging innovation culture and cultivating innovative behaviour which was rarely found in current literature. Findings of this study are beneficial to university administrators in planning appropriate actions to initiate and sustain innovative behaviour among their students.